Statistics For Social Sciences - Rajaretnam, T. (Los Angeless Sage Publicatiom, 2016)
A comprehensive guide to the practical applications of statistics in social sciences. It brings out the relevance of statistical tools and methods in social sciences. Describing the various statistical techniques, it highlights their purpose and application along with a brief overview on how to interpret results and draw inferences.
Include Index, Bibliography and Appendix
Keywords: Social sciences--Research--Methodology -- Social sciences--Statistical methods